Analisis Pengendalian Kualitas Produk Berdasarkan Pendekatan Six Sigma Dengan Metode DMAIC di PT XYZ - Mellani Dwi Wulandari (Peneliti.net, 2022)
PT XYZ is acompany that it concern to make transformator unit. The problem of this company face how to eliminated the existing wastes that is found in the production processes such as the non value added activities and the existing defect products (30,3%) wchich its unmatch to the company standards. These things have made lateness to to fulfil the lead time to produce an amount of product demand. The purpose of this research is the applying of quality control concepts to identyfing and eliminating the waste on the production floor in lead time shortly. The result of this research is the lean condition in production with process cycle efficiency about 82 %. The quality number for the inspection II and III step is 3,38 & 4,01. The improvement suggestion that can be given are the works procedure applying an the coil rolling section, and the 5s methods applying, machine maintenances, periodically operator training and supervision. They are the important thing which the compony have to concern about toward the future. On the other hand, work place management is also suggested and the five non-value-added activities should be eliminated